2019
DOI: 10.1083/jcb.201808065
|View full text |Cite
|
Sign up to set email alerts
|

MAP7 family proteins regulate kinesin-1 recruitment and activation

Abstract: Kinesin-1 is responsible for microtubule-based transport of numerous cellular cargoes. Here, we explored the regulation of kinesin-1 by MAP7 proteins. We found that all four mammalian MAP7 family members bind to kinesin-1. In HeLa cells, MAP7, MAP7D1, and MAP7D3 act redundantly to enable kinesin-1–dependent transport and microtubule recruitment of the truncated kinesin-1 KIF5B-560, which contains the stalk but not the cargo-binding and autoregulatory regions. In vitro, purified MAP7 and MAP7D3 increase microtu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
112
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 52 publications
14
112
0
Order By: Relevance
“…5B). We believe that this stimulation of the motor binding can occur in solution because we were not able to detect any association of the KBD with MTs either in vivo or in vitro, as also recently shown by other groups using rat and human Ensconsin (MAP7) (Hooikaas et al, 2019;Tymanskyj et al, 2018). Interestingly, this interaction between Ensconsin and KHC is observed in cell extracts, with or without polymerized microtubules (this work).…”
Section: Mechanisms Of Ensconsin Stimulation Of Kinesin-1 Recruitmentsupporting
confidence: 60%
See 2 more Smart Citations
“…5B). We believe that this stimulation of the motor binding can occur in solution because we were not able to detect any association of the KBD with MTs either in vivo or in vitro, as also recently shown by other groups using rat and human Ensconsin (MAP7) (Hooikaas et al, 2019;Tymanskyj et al, 2018). Interestingly, this interaction between Ensconsin and KHC is observed in cell extracts, with or without polymerized microtubules (this work).…”
Section: Mechanisms Of Ensconsin Stimulation Of Kinesin-1 Recruitmentsupporting
confidence: 60%
“…Second, both proteins colocalize on the internal MT network of Drosophila oocyte egg chambers (Sung et al, 2008, this paper). Third, Ensconsin C-terminal domain (KBD) and Kinesin-1 can interact in vivo (Hooikaas et al, 2019;Metzger et al, 2012, this study). Based on the current literature, the recruitment model suggests that Ensconsin bound to the MT lattice (via the MBD) serves as a direct recruitment platform for Kinesin-1 (Fig.…”
Section: Mechanisms Of Ensconsin Stimulation Of Kinesin-1 Recruitmentmentioning
confidence: 69%
See 1 more Smart Citation
“…P < 0.0001 (***) using a student's t-test for KIF1A alone vs. KIF1A + MAP7, tau, MAP2, DCX, and DCLK1 and for each MAP combination. P = 0.0034 (**) for KIF1A alone vs. 26,41 . Similarly, prior studies have reported a direct interaction between kinesin-3 and both DCX 46 and DCLK1 6 .…”
Section: Map9 Enables Kinesin-3 Progression On the Lattice Due To A Tmentioning
confidence: 99%
“…In neurons, kinesin-3 and dynein drive various cargoes within both axons and dendrites, while likely that MAP2 affects kinesins and dynein akin to tau. MAP7 is important for a range of kinesin-1 functions in vivo [36][37][38][39][40] , and has been shown in vitro to directly bind and recruit kinesin-1 to the microtubule lattice 26,41,42 . Kinesin-1 is most likely able to navigate the tau-rich axon in part due to the presence of MAP7, which displaces tau from the microtubule 26 .…”
Section: Introductionmentioning
confidence: 99%